The Fabrication and Evaluation of a Potential Biomaterial Produced with Stem Cell Sheet Technology for Future Regenerative Medicine - Shukui Zhou; Ying Wang; Kaile Zhang; Nailong Cao; Ranxing Yang; Jianwen Huang; Weixin Zhao; Mahbubur Rahman; Hong Liao; Qiang Fu (Hindawi Limited, 2020)
To date, the decellularized scaffold has been widely explored as a source of biological scaffolds for regenerative medicine. However, the acellular matrix derived from natural tissues and organs has a lot of defects, including the limited amount of autogenous tissue and surgical complication such as risk of blood loss, wound infection, pain, shock, and functional damage in the donor part of the body. In this study, we prepared acellular matrix using adipose-derived stem cell (ADSC) sheets and evaluate the cellular compatibility and immunoreactivity. The ADSC sheets were fabricated and subsequently decellularized using repeated freeze-thaw, Triton X-100 and SDS decellularization. Oral mucosal epithelial cells were seeded onto the decellularized ADSC sheets to evaluate the cell replantation ability, and silk fibroin was used as the control. Then, acellular matrix was transplanted onto subcutaneous tissue for 1 week or 3 weeks; H&E staining and immunohistochemical analysis of CD68 expression and quantitative real-time PCR (qPCR) were performed to evaluate the immunogenicity and biocompatibility. The ADSC sheet-derived ECM scaffolds preserved the three-dimensional architecture of ECM and retained the cytokines by Triton X-100 decellularization protocols. Compared with silk fibroin in vitro, the oral mucosal epithelial cells survived better on the decellularized ADSC sheets with an intact and consecutive epidermal cellular layer. Compared with porcine small intestinal submucosa (SIS) in vivo, the homogeneous decellularized ADSC sheets had less monocyte-macrophage infiltrating in vivo implantation. During 3 weeks after transplantation, the mRNA expression of cytokines, such as IL-4/IL-10, was obviously higher in decellularized ADSC sheets than that of porcine SIS. A Triton X-100 method can achieve effective cell removal, retain major ECM components, and preserve the ultrastructure of ADSC sheets. The decellularized ADSC sheets possess good recellularization capacity and excellent biocompatibility. This study demonstrated the potential suitability of utilizing acellular matrix from ADSC sheets for soft tissue regeneration and repair.